2020
DOI: 10.1002/cctc.201902372
|View full text |Cite
|
Sign up to set email alerts
|

Hydroconversion of Perhydrophenanthrene over Bifunctional Pt/H‐USY Zeolite Catalyst

Abstract: In petroleum refining, middle distillates are produced via hydroisomerization/hydrocracking processes using bifunctional catalysts often containing ultrastable Y (USY) zeolite. Petroleum fractions serving as feedstock for hydrocracking processes contain a majority of (poly)cyclic hydrocarbon molecules. Few studies on reaction mechanisms of hydrocracking of such polycyclic compounds are available. In this study the tricyclic phenanthrene molecule was used as model compound. Phenanthrene was hydrogenated on a Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 48 publications
0
28
1
1
Order By: Relevance
“…The results revealed that Mo promoted sites (NiMoS) corresponded to only 15% of the overall Mo in the catalyst. Concomitantly, the deposition of Pt in either the HUSY zeolite or in the shaped extrudates leads to metal dispersions between 40 27 and 90% 28,45,46 , with shaped supports typically featuring higher dispersions. Potentially, because ionic exchange is preferred in the latter whereas incipient wetness impregnation is commonly employed in powder zeolites.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that Mo promoted sites (NiMoS) corresponded to only 15% of the overall Mo in the catalyst. Concomitantly, the deposition of Pt in either the HUSY zeolite or in the shaped extrudates leads to metal dispersions between 40 27 and 90% 28,45,46 , with shaped supports typically featuring higher dispersions. Potentially, because ionic exchange is preferred in the latter whereas incipient wetness impregnation is commonly employed in powder zeolites.…”
Section: Discussionmentioning
confidence: 99%
“…The powder was mixed with an alumina binder (Pural SB3), furnished by Sasol, and extruded, according to a protocol described elsewhere. 39,42 Zeolite loading corresponded to 1 or 3 wt% of the dried support. The low zeolite loadings were chosen in order to obtain activity values of the same order of magnitude as a silica-alumina catalyst.…”
Section: Preparation and Characterization Of Catalystsmentioning
confidence: 99%
“…Further details on the preparation of catalysts may be found in previous work. 39 Pt-Based catalysts were calcined at 520 °C for 2 h, under an air flow of 1 NL h −1 g catalyst −1…”
Section: Preparation and Characterization Of Catalystsmentioning
confidence: 99%
See 2 more Smart Citations